Teaching information literacy : 50 standards-based exercises for college students - Burkhardt, Joanna M.; MacDonald, Mary C.; Rathemacher, Andree J. (Chicago : American Library Association, 2010)
'Covering the basics of planning, collecting, and evaluating, each of the 50 standards-based exercises in this book address one or more of the ACRL Information Literacy Competency Standards for Higher Education and promote conceptual and applied skills via active learning, problem-based learning, and resource-based learning.'--[back cover]
Includes bibliographical references and index.
Keywords: Information literacy -- Study and teaching (Higher) -- Problems, exercises, etc; Information resources -- Evaluation -- Study and teaching (Higher).; Research -- Methodology -- Study and teaching (Higher).; Electronic information resource literacy -- Study and teaching (Higher).; Computer network resources -- Evaluation -- Study and teaching (Higher).; Internet research -- Study and teaching (Higher).; Library orientation for college students